Differential effects of central administration of relaxin‐3 on food intake and hypothalamic neuropeptides in male and female rats. (18th August 2015) - Calvez, J.; Lenglos, C.; de Ávila, C.; Guèvremont, G.; Timofeeva, E.
<x xml:space="preserve">Abstract</x> Relaxin‐3 produces stronger orexigenic effects and stronger activation of orexin mRNA expression in the lateral hypothalamus in female rats. <boxed-text content-type="graphic" id="gbb12236-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>